Study the expression rate and methylation of TIMP-3 gene in the blood samples of people suffering from gastric cancer - Karimi Shahrivar, Zahra; Moslemi, Elham (Bionatura, 2022)
TIMPs inhibit the necrosis factor converting enzyme of alpha tumor and induce planned cellular death. Methylation in TIMP3 promoter would cause tumor progress in cancer. The present research seeks to study the expression rate and methylation of the TIMP3 gene in the blood of individuals who have gastric cancer. The present research uses MS PCR and Real-time PCR to study the expression rate and methylation of the TIMP3 gene, which has recently attracted much attention in gastric cancer. In this research, we have compared the blood samples of those with gastric cancer and ordinary people among Iranian patients. The expression rate of TIMP3 in the blood samples obtained from those who have gastric cancer has decreased significantly compared to the blood samples obtained from ordinary people. A significant correlation was also observed between the expression rate of this gene, age and methylation in gastric cancer. Methylation and expression levels of the TIMP3 gene were statistically significant in patient samples compared to healthy subjects, and decreased methylation and increased expression of this gene in healthy individuals indicated the role of altered gene expression in gastric cancer. Keywords. Gastric cancer; TIMPs; Methylation; Real-time PCR.